Transformational Outcome-Based Education in Islamic Studies: A Learning Design Implemented in the Ethics Course - Izzah Faizah Siti Rusydati Khaerani; Iu Rusliana; Dindin Moh Saepudin (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study examines the implementation of a Transformational Outcome-Based Education (OBE) model in Dirāsah Islāmiyah, situating Islamic moral education within contemporary outcomes-based pedagogical frameworks. The study aims to analyse the instructional design, explore implementation challenges—particularly in assessing affective learning outcomes—and evaluate the Continuous Quality Improvement (CQI) mechanisms embedded in the process. A qualitative case study approach was employed in an Ethics (Ilmu Akhlak) course at UIN Sunan Gunung Djati Bandung. Data were collected over one semester through participatory observation, in-depth interviews with one lecturer and 33 students, and document analysis, including the Semester Learning Plan and student portfolios. The findings reveal that the Transformational OBE model was operationalised through strong constructive alignment, integrating Problem-Based Learning (PBL) and Project-Based Learning (PjBL) to promote critical reflection consistent with Mezirow’s Transformative Learning Theory. Reflective journals emerged as the primary instrument for assessing the internalisation of moral and spiritual values. However, significant challenges were identified, including students’ initial resistance to reflective practices and lecturers’ difficulties in objectively evaluating affective domains. The CQI mechanism, implemented through the Plan–Do–Check–Act (PDCA) cycle, played a crucial role in enabling iterative pedagogical refinement. In conclusion, this study demonstrates that integrating spiritual objectives into the OBE framework is both feasible and pedagogically valuable, while also highlighting the need for more robust affective assessment strategies in Islamic higher education contexts.